MENEMUKENALI BAHASA FIGURATIF DALAM CERITA PENDEK "KISAH I SWARNANGKARA SI PENJAGA HUTAN" KARYA I NYOMAN SUARJANA - Ni Komang Tri Jayanti; I Made Joni Fristyawan (Kulturistik: Jurnal Ilmu Bahasa dan Budaya, 2024)
This research aims to identify the types of figurative language found in the short story titled "Kisah I Swarnangkara Si Penjaga Hutan" and the cultural meanings embedded within it. The short story, authored in the Indonesian language by I Nyoman Suarjana, serves as the primary data source for this study. Data collection methods employed include documentation and note-taking techniques. A qualitative approach is utilized to analyze the data based on Keraf's theory (2011). Meanwhile, the method of data presentation in this study is informal, employing descriptive words. The findings of this research reveal the presence of six types of figurative language utilized in this short story, including simile, metaphor, personification, synecdoche, sarcasm, and irony. These six figurative language styles represent cultural meanings associated with family bonds, hard work, simplicity, independence, and the relationship between humans and nature.